1994
DOI: 10.1152/ajpcell.1994.266.4.c967
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of hyperthermia on macrophage interleukin-6 and tumor necrosis factor-alpha expression

Abstract: The pyrogenic cytokines tumor necrosis factor-alpha (TNF-alpha) and interleukin-6 (IL-6) appear in the circulation during infections and injuries, but TNF-alpha and IL-6 are regulated differently in macrophages. We compared the effects of elevated temperatures within the usual febrile range on the expression of TNF-alpha and IL-6 in vitro in lipopolysaccharide (LPS)-stimulated human macrophages derived from peripheral blood monocytes (HuMoM phi). During an 18-h incubation at 37 degrees C with 5 ng/ml LPS, thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
80
1
2

Year Published

1998
1998
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(90 citation statements)
references
References 22 publications
6
80
1
2
Order By: Relevance
“…This finding led us to conclude that heat shock inhibits LPSinduced IL-6 expression in mouse cells. Previous reports showed that IL-6 expression was not inhibited by hyperthermia in human macrophages treated with LPS (10) and that hyperthermia promoted IL-6 production in human enterocytes (47). Furthermore, treatment with hyperthermia in mice resulted in an increase in serum IL-6 levels (48).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This finding led us to conclude that heat shock inhibits LPSinduced IL-6 expression in mouse cells. Previous reports showed that IL-6 expression was not inhibited by hyperthermia in human macrophages treated with LPS (10) and that hyperthermia promoted IL-6 production in human enterocytes (47). Furthermore, treatment with hyperthermia in mice resulted in an increase in serum IL-6 levels (48).…”
Section: Discussionmentioning
confidence: 95%
“…These beneficial roles of fever are mediated partly by a strengthening of immune surveillance through lymphocyte trafficking (7), as well as by the suppression of pyrogenic and inflammatory cytokines, such as IL-1 and TNF-a, in the cell (8)(9)(10) and body (6,11). However, it is unclear whether hyperthermia inhibits the expression of IL-6 as it affects IL-6 and TNF-a expression differently in macrophages (10).…”
mentioning
confidence: 99%
“…Mean Ϯ SE; n ϭ 6; ‫,ء‬ P Ͻ 0.05 compared with the "no fever" mice. (11,12,18). We also reported that increasing core temperature in LPS-challenged mice accelerated and enhanced an early, self-limited pulse of TNF-␣ in plasma but subsequently suppressed persistent TNF-␣ expression and enhanced the expression of IL-6 (17,18).…”
Section: Resultsmentioning
confidence: 99%
“…It is well documented that HSP induction within the cell can downregulate the inflammatory cascade by reducing TNF-␣ production to inflammatory stimuli (11,18,36,73,79). The mechanism responsible for the upregulation of HSP during inflammatory stimuli results from serine kinase and mitogen-activated protein kinase (MAPK) activation of the NF-B pathway, coupled with the production of reactive oxygen species and subsequent oxidative stress in the mitochondria.…”
Section: Discussionmentioning
confidence: 99%